PENGARUH KEPEMIMPINAN SERTA PELATIHAN TERHADAP KINERJA CLEANING SERVICE PADA PT. GSS DI INSTALASI BEDAH SENTRAL RSUD AJI MUHAMMAD PARIKESIT TENGGARONG - Irawn, Dedi; Noorhya Akhmar Ramadhan Putri, Eva Noorhya Akhmar Ramadhan Putri; Zainuddin, Muhammad (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2024)
Dedi Irawan (2024) The Effect of Product Quality and Service Quality on Indihome Internet Customer Satisfaction in Residents in Griya Tambak Tenggarong Rail Housing, The objectives of this study are The objectives of this study are as follows: To determine the influence of leadership and motivation variables simultaneously and significantly on the performance of the cleaning service team at PT. GSS at the Central Surgical Installation of Aji Muhammad Parikesit Hospital To determine the influence of leadership variables partially and significantly on the performance of the cleaning service team at PT. GSS at the Central Surgical Installation of Aji Muhammad Parikesit Hospital To find out the training variables partially and significantly on the performance of the cleaning service team at PT. GSS at the Central Surgical Installation of Aji Muhammad Parikesit Hospital The number of samples in this study was 7 people The results of the study were obtained that the variables of leadership and training had a positive and significant effect on the morale of PT. GSS at the central surgical installation of Aji Muhammad Parikesit Hospital. Leadership variables have a positive and significant effect on the morale of PT. GSS at the central surgical installation of Aji Muhammad Parikesit Hospital. Training variables have a positive and significant effect on the morale of PT. GSS at the central surgical installation of Aji Muhammad Parikesit Hospital.